Patterns of HCI Design and HCI Design of Patterns Bridging HCI Design and Model-Driven Software Engineering - Seffah, Ahmed (Human-Computer Interaction Series, 2015)
As interactive systems are quickly becoming integral to our everyday lives, this book investigates how we can make these systems, from desktop and mobile apps to more wearable and immersive applications, more usable and maintainable by using HCI design patterns. It also examines how we can facilitate the reuse of design practices in the development lifecycle of multi-devices, multi-platforms, and multi-contexts user interfaces.   Effective design tools are provided for combining HCI design patterns and User Interface (UI) driven engineering to enhance design whilst differentiating between UI and the underlying system features. Several examples are used to demonstrate how HCI design patterns can support this decoupling by providing an architectural framework for pattern-oriented and model-driven engineering of multi-platforms and multi-devices user interfaces. Patterns of HCI Design and HCI Design of Patterns is for students, academics and Industry specialists who are concerned with user interfaces and usability within the software development community.